Kepatuhan Bidan dalam Penerapan SOP Pemotongan Tali Pusat Pada Bayi Baru Lahir - Rosmadewi Rosmadewi; Mugiati Mugiati (Jurnal Kesehatan, 2019)
Pinning and cutting the umbilical cord is a standard procedure that is always done when the baby is born. The benefits of delaying cord clamping for infants include the opportunity for red blood, stem cells, and immune cells to be transmitted to the baby's body outside the uterus. As for mothers, delaying cord clamping can reduce the complications of bleeding. This study aims to determine the Midwife's Compliance Level in the Implementation of SOP Cutting the Cord in Newborns in Bandar Lampung City. This type of research is correlation analytic with a cross-sectional approach. The research subjects are midwives who provide birth assistance services in the city of Bandar Lampung with a total of 131 people, the sample in this study was the total population. Data collection uses primary data. Univariate data analysis uses percentages and bivariate analysis uses chi-square. The results showed that midwives' level of compliance in implementing SOP of umbilical cord-cutting in newborns in the category of non-compliance was 83 respondents (63.4%), midwife knowledge was categorized as good as 102 respondents (77.9%) and the attitude of midwives in the category of no support as many as 76 respondents (58.02%). There is a significant relationship between midwives 'attitudes and midwives' compliance in the adoption of umbilical cord cutting SOPs in newborns and there is no relationship between midwives 'knowledge and midwives' level of compliance in implementing umbilical cord cutting SOPs. Professional organizations (IBI Bandar Lampung City) and midwives coordinator of the local health center need to program supervision to midwives who provide delivery assistance to always implement the SOP cutting the umbilical cord on newborns.